Pengaruh Motivasi dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT Air Minum Murakata Lestari Kabupaten Hulu Sungai Tengah - Supiani; Irwansyah (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: This research is to know and test the influence of Motivation and Job Satisfaction on Employee Performance at PT. Air Minum Murakata Lestari (Perseroda) Kabupaten Hulu Sungai Tengah. Using a quantitative approach. Samples were selected as many as 56 employees selected by Saturated Sampling Technique. Data collection used a questionnaire while data analysis used the SPSS program. The results of this study prove 1) Motivation has a partial significant effect on Emplomantyee Performance, 2) Job Satisfaction has a partial significant effect on Employee Performance, 3) Motivation and Job satisfaction have a significant simultaneous effect on Employee Performance. The implementation in this study is that to improve employee performance it is necessary to pay attention to motivation and job satisfaction Keywords: Motivation, Job Satisfaction, Employee Performance